Taxonomic status of Protankyra ramiurna and Protankyra benedeni (Holothuroidea: Apodida: Synaptidae) - Prata, Jéssica; Borges, Michela; Manso, Cynthia L. C.; Christoffersen, Martin Lindsey (Zootaxa, 2017)
This study presents a review of the species Protankyra ramiurna Heding, 1928 and Protankyra benedeni (Ludwig, 1881) from the Brazilian coast. Some authors consider that these two taxa represent a single variable species. Our comparative analysis of external characters, anatomy and ossicle morphology indicates that they represent distinct species. This is the first record of Protankyra ramiurna from Brazil.